Evaluasi Learning Management System Pada E-Campus Menggunakan End User Computing Satisfaction Di Universitas Bina Insani - Stepphanus Manurung; Nadya Safitri (Prosiding SISFOTEK, 2024)
E-Campus is a complete web-based (enterprise) application that helps manage/administrate academic activities at an institution of higher education (University, College, Institute, Polytechnic, Academy, etc.). The management in question includes data collection (new students, lecturers, faculties, study programs, courses, curriculum, etc.), scheduling lectures, teaching and learning activities (attendance, material delivery, quiz, UAS, UTS, etc.), to data reporting. The features of the ecampus are still not felt by students in their use. This evaluation uses the EUCS (End User Computing Satisfaction) method which uses 5 dimensions, namely; Content, Accuracy, Format, Ease Of Use, Timeliness. The population in this study were actived users members, namely Bina Insani University students with a total sample size of 96 respondents. The media for distributing questionnaires is using google forms which are distributed via whatsapp and instagram as well as directly to activated users. The analysis method used is SEM (Structural Equation Modeling) with the Partial Least Square (PLS) Method. The calculation tool used is SmartPLS 3 student version. The result of this analysis is the acceptance of the five hypotheses tested. So that these results indicate that Ease Of Use and Timeliness are proven to have a positive and significant effect on the use of User Satisfaction. This Ease Of Use test value is evidenced by a path coefficient value of 0.32 and a t-statistic value of 2.605. Timeliness is proven to have a positive and significant effect on User Satisfaction. This is evidenced by the path coefficient value of 0.29 and the T-Statistic value of 2.519. While the Content, Ease Of Use, Format variables do not provide significant results on user satisfaction.